TERAPI BERMAIN UNTUK MENGATASI TRAUMA SISWA MTS PASCA BENCANA TANAH LONGSOR JOMBANG - Dewa, Reysha Zhulfirda Anggara; Rini, Amanda Pasca; Rina, Amherstia Pasca (Nindikayla Institute, 2023)
Disasters have quite fatal consequences for humans, one of which is the psychological impact, especially trauma. Trauma can occur anytime, anywhere and in any form. Trauma can affect physical and psychological conditions. The method used in this community service activity is the application of psychological trauma healing interventions through play therapy to overcome the trauma of MTS Anjasmoro students after the landslide disaster. The results of psychological trauma healing intervention through play therapy to overcome the trauma of MTS Anjasmoro students after the landslide disaster went smoothly with every participant present enthusiastically following the activity from start to finish. Students also understand what trauma is, what the signs and symptoms are, what the causes are, and what to do when experiencing trauma. Apart from that, psychological trauma healing interventions through play therapy have been proven to be able to reduce the level of trauma experienced by students after disasters in areas prone to landslides